All-acrylic superelastomers: facile synthesis and exceptional mechanical behavior. Issue 2 (27th October 2017) - Lu, Wei; Goodwin, Andrew; Wang, Yangyang; Yin, Panchao; Wang, Weiyu; Zhu, Jiahua; Wu, Ting; Lu, Xinyi; Hu, Bin; Hong, Kunlun; Kang, Nam-Goo; Mays, Jimmy
Abstract : All-acrylic multigraft copolymers made by a facile synthesis procedure exhibit elongation at break >1700% and strain recovery behavior far exceeding those of commercial acrylic and styrenic triblock copolymers. Abstract : All-acrylic multigraft copolymers, poly(butyl acrylate)- g -poly(methyl methacrylate), synthesized using a facile grafting-through methodology, exhibit elongation at break (>1700%) and strain recovery behavior far exceeding those of any commercial acrylic (∼500%) and styrenic (∼1000%) triblock copolymers to date. One-batch anionic polymerization of methyl methacrylate (MMA) using the sec -butyl lithium/ N -isopropyl-4-vinylbenzylamine ( sec -BuLi/PVBA) initiation system gives PMMA macromonomers with quantitative yield, short reaction time, and using simple synthetic procedures. These new all-acrylic superelastomers and the simple synthetic approach greatly expand the range of potential applications of all-acrylic thermoplastic elastomers (TPEs).